2013
DOI: 10.1101/gr.146886.112
|View full text |Cite
|
Sign up to set email alerts
|

Widespread and extensive lengthening of 3′ UTRs in the mammalian brain

Abstract: Remarkable advances in techniques for gene expression profiling have radically changed our knowledge of the transcriptome. Recently, the mammalian brain was reported to express many long intergenic noncoding (lincRNAs) from loci downstream from protein-coding genes. Our experimental tests failed to validate specific accumulation of lincRNA transcripts, and instead revealed strongly distal 3′ UTRs generated by alternative cleavage and polyadenylation (APA). With this perspective in mind, we analyzed deep mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
383
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(420 citation statements)
references
References 42 publications
30
383
0
Order By: Relevance
“…Other recent findings also support the view that UTRs may play a previously underappreciated role in establishing specific functions of tissues and organs: Throughout the evolution of animals, UTR length has increased along with morphological complexity (40). The brain, arguably the most complex tissue in humans, has much longer UTRs than other tissues (14). The use of emerging technologies that allow precise mapping of transcript start and end sites (41) is expected to provide more insight into this largely unexplored terrain.…”
Section: Differential Exon Usage Provides Versatile Mechanisms To Achmentioning
confidence: 59%
See 1 more Smart Citation
“…Other recent findings also support the view that UTRs may play a previously underappreciated role in establishing specific functions of tissues and organs: Throughout the evolution of animals, UTR length has increased along with morphological complexity (40). The brain, arguably the most complex tissue in humans, has much longer UTRs than other tissues (14). The use of emerging technologies that allow precise mapping of transcript start and end sites (41) is expected to provide more insight into this largely unexplored terrain.…”
Section: Differential Exon Usage Provides Versatile Mechanisms To Achmentioning
confidence: 59%
“…Tissue-dependent usage (TDU) of exons also affects noncoding parts of transcripts, such as 3′ UTRs, which often contain binding sites for micro-RNAs and RNAbinding proteins (13). For example, the brain tends to have transcripts with much longer UTRs than other tissues (14).…”
mentioning
confidence: 99%
“…4). Polyadenylation-site sequencing (PAS-seq) revealed the intergenic regions to represent strongly distal 3′ UTRs 25 (Fig. 2b).…”
Section: Stau1 Binds Paired Alu Elements In 3′ Utrsmentioning
confidence: 99%
“…It can be difficult to predict the functionality of incomplete transcript models. For example, it has been reported that numerous GENCODE lncRNAs may actually represent 39 UTR sequence from protein-coding genes (Miura et al 2013), while a putative CDS could be recharacterized as an NMD candidate if the model is extended at the 39 end. For these reasons, protocols have been devised that capture the true ends of transcripts, i.e., the transcription start site (TSS) and polyadenylation (polyA) site.…”
Section: New Technologies Can Aid Transcript Capture and Completionmentioning
confidence: 99%